"Don't think, just shoot" – The paradox of shooting three-point shots in basketball. Issue 6 (2nd November 2022) - Lidor, Ronnie; Lipshits, Lior; Arnon, Michal; Bar-Eli, Michael
ABSTRACT: A two-phase study was conducted on shooting three-point shots in basketball in pressure/no-pressure game situations. In Phase 1 – a subjective approach, our aim was to discover what the players and coaches thought about shooting beyond the three-point arc when the shooters were performing under defensive pressure or when they were free of such pressure. In Phase 2 – an analysis of shooting success, we examined the actual success (i.e., percentage of successful shots) of shooting three-point shots under these two situations. In Phase 1, 97 Division 1 male basketball players and 12 elite coaches were asked how they perceived shooting three-point shots in various game situations. In Phase 2, the success of 382 three-point shots taken in actual Division 1 games was analyzed. The shots were classified by four expert coaches into two categories – shots taken in free-of-defense and shots taken in under-pressure game situations. The success of the two classified shots was analyzed under 10 conditions. Expected results were found in Phase 1 – both players and coaches believed that the success of three-point shots is higher when the shots are taken when the shooter is free of defense. In Phase 2, a surprising finding was revealed: shooting success was higher when the players shot under defensive pressure. We discuss the data in line with Kahneman's (2011), Thinking, fast and slow, model, and propose a number of practical implications for coaches who are preparing their three-point shooters to deal with real game situations.